Secure Blockchain-Internet of Vehicles (B-IoV) Mechanism using DPSO and M-ITA Algorithms. (February 2022) - Devi, Anju; Rathee, Geetanjali; Saini, Hemraj
Abstract: The Internet of Vehicles (IoV) is introduced to transfer/exchange the data among roadside units and vehicles through various smart devices in real time scenarios. However, the past works in IoV leads to various transparencies, security and privacy concerns while communicating and transferring the information among each other. This paper has proposed a blockchain-based trustworthy framework for vehicular networks by reducing the security issues like trust issue and quickly updating the status of vehicles via blockchain ledger. The proposed scheme provides the security at two different stages; 1) the first stage calculates the candidate's trust degree, data quality, and privacy via other vehicles through a Modified-Two-stage Auction Algorithm (M-ITA) scheme to select the trusted miners and maximize their utilities, and 2) in the second stage, a block selection method is introduced that uses the discrete particle swarm optimization (DPSO). In every time-slot, only selected miners validate the blocks and updated their position dynamically. The performance of proposed framework is analyzed through numerical analysis by improving the trustworthiness for data sharing in blockchain-based IoV using various security parameters.